Beam-switching planar parasitic antenna array - Imran, Zohaib; Panagamuwa, Chinthana (2014 Loughborough Antennas and Propagation Conference (LAPC), 2014)
This paper presents a planar parasitic antenna array that achieves beam switching operation by using the Yagi-Uda principle. The treatment of the Yagi-Uda principle in this paper employs closely-spaced directors as opposed to the traditional inter-director spacing, and this shows advantages in terms of the front-to-back ratio (F/B) and size. The beam switching has been realized in 3 principal beam directions through the selective switching of 4 PIN Diodes on the antenna structure. A fully functional antenna using PIN Diodes with an optimized biasing line arrangement and circuitry has been fabricated, and the results obtained through measurement show good agreement with simulation results. The antenna shows good impedance match and beam-switching characteristics in the Wi-Fi frequency band, opening up the possibility of the antenna's use in practical applications.